NCR3/NKp30 contributes to pathogenesis in primary Sjögren’s syndrome - Rusakiewicz, Sylvie (Sci Transl Med, 2013)
Primary Sjögren’s syndrome (pSS) is a chronic autoimmune disease characterized by a lymphocytic exocrinopathy. However, patients often have evidence of systemic autoimmunity and they are at markedly increased risk for the development of non- Hodgkin’s lymphoma. Similar to other autoimmune disorders, a strong interferon (IFN) signature is present among subsets of pSS patients, though the precise etiology remains uncertain. NCR3/NKp30 is a NK-specific activating receptor regulating the cross-talk between NK and dendritic cells and type II IFN secretion. We performed a case-control study of genetic polymorphisms of the NCR3/NKp30 gene and found that rs11575837 (G>A) residing in the promoter was associated with reduced gene transcription and function as well as protection to pSS. We also demonstrated that circulating levels of NCR3/NKp30 were markedly increased among pSS patients compared with controls and correlated with higher NCR3/NKp30 but not CD16-dependent IFN-γ secretion by NK cells. Excess accumulation of NK cells in minor salivary glands correlated with the severity of the exocrinopathy. B7H6, the ligand of NKp30, was expressed by salivary epithelial cells. These findings suggest that NK cells may promote an NKp30-dependent inflammatory state in salivary glands, and that blockade of the B7H6/NKp30 axis could be clinically relevant in pSS.